Medication errors with influencing factors of polypharmacy among elderly patients using Calcium Chanel Blockers. - Nesar, Shagufta; Shoaib, Muhammad Harris; Rafiq, Kiran; Mughal, Muhammad Azhar; Mumtaz, Tayyaba; Younus, Ishrat; Akram, Afra (International Journal of Endorsing Health Science Research, 2022)
Background: Geriatrics refers to age-related health changes and consequently causes complications in polypharmacy, generalizing prescribing patterns. The study aimed to investigate the pervasiveness of medication inaccuracies along with drug interactions. Methodology: Out of 450 prescriptions only 210 were selected that contained Calcium Channel Blocker (CCB) and other drugs. Drug-drug interactions were articulated by Micromedex 2.0, and the harm score was determined by National Coordinating Council for Medication Error Reporting and Prevention. Results: The outcomes revealed that 645 medication errors were identified and multiple errors were present in a single prescription. The most frequent error was unstated patient's weight (98.6%) proceeds from drug-drug interactions (66.7%). According to the harm score, 36.66% of prescriptions were placed in category D, there was a statistically significant association between the drug-drug interaction and the number of prescribed drugs (p<0.0001). Conclusion: The prime solution is that the physicians should be facilitated withal trainings about drug interactions and prescription writing skills according to WHO guidelines or other recognized standards.